Public debt vs economic growth / Nur Atiqah Zainal Abidin - Zainal Abidin, Nur Atiqah (Faculty of Business Management, 2018)
Economic growth (measured by gross domestic product) can be affected both positively and negatively by public debts. The higher the level of public debt, the lower the economic growth of the company. Basically, when a government is having a huge debt, they tend to have a limited spending towards the economic developments. Due to that circumstances, this study was conducted in order to investigate the relationship between the public debts and economic growth in Malaysia. This study was based on secondary data obtained from World Data Bank and DataStream using the time range of 30 years from 1987-2016. The variables used in this study is Gross Domestic Product (GDP) as the proxy to economic growth and a group of public debt elements were used as independent variables. The data were analysed using multiple linear regression to investigate the relationship between the variables. As a result this study finds that the public debt and all the factors are both has positive and negative relationship.